2005
DOI: 10.1080/03009740510026715
|View full text |Cite
|
Sign up to set email alerts
|

Detection of elevated Nε‐carboxymethyllysine levels in muscular tissue and in serum of patients with fibromyalgia

Abstract: In the interstitial connective tissue of fibromyalgic muscles we found a more intensive staining of the AGE CML, activated NF-kappaB, and also higher CML levels in the serum of these patients compared to the controls. RAGE was only present in FM muscle. AGE modification of proteins causes reduced solubility and high resistance to proteolytic digestion of the altered proteins (e.g. AGE-modified collagens). AGEs can stimulate different types of cells by activation of the transcription factor NF-kappaB, mediated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 15 publications
2
23
0
Order By: Relevance
“…In addition, no inflammatory changes have been described in muscle biopsy samples from FMS patients. However, it has been reported that immunoreactivity for the advanced glycation end product (AGE), N ε -carboxymethyllysine (CML), is elevated in biopsy samples from the biceps brachii muscle of FMS patients compared to controls [500]. The CML receptor RAGE and its downstream effector, activated NF-kB, along with CD68+ cells (monocytes/macrophages) were detectable in FMS samples, but only rarely could be observed in control samples.…”
Section: Muscle Abnormalitiesmentioning
confidence: 98%
“…In addition, no inflammatory changes have been described in muscle biopsy samples from FMS patients. However, it has been reported that immunoreactivity for the advanced glycation end product (AGE), N ε -carboxymethyllysine (CML), is elevated in biopsy samples from the biceps brachii muscle of FMS patients compared to controls [500]. The CML receptor RAGE and its downstream effector, activated NF-kB, along with CD68+ cells (monocytes/macrophages) were detectable in FMS samples, but only rarely could be observed in control samples.…”
Section: Muscle Abnormalitiesmentioning
confidence: 98%
“…They include appearance of ragged red fibers and moth-eaten fibers, inflammatory infiltrates, DNA fragmentation in muscle fibers, muscle perfusion deficits (confirmed by the reduction in pH related to ischemia), reduction in phosphorylation potential and total oxidative capacity, and increase in inflammatory mediators and cytokines as well as advanced glycation end products [17].…”
Section: Peripheral and Central Sensitization In Fm And Migrainementioning
confidence: 99%
“…The presence of local alterations of muscular collagen in FM, with an increased content of advanced glycation end products causing a higher resistance to proteolysis, has been demonstrated and discussed (31).…”
Section: Discussionmentioning
confidence: 97%